A „Lélek által való nemesedés” szolgálata. Református kollégiumok küldetése a tehetségek támogatásában - FEHÉR, Ágota (Studia Universitatis Babes-Bolyai Theologia Reformata Transylvanica, 2022)
Service of “Nobility through the Spirit”. The Mission of Reformed Colleges to Support Talent. In the community of Reformed institutions, children’s growth is accompanied by educators whose mission is a call from God, in the spirit of which they seek to convey the word of the Bible to children. The main message of nurturing talent is to help all students become aware of the abilities they have received from God personally. Reformed colleges play a special role in this and build on significant historical traditions, and see nurturing talent as a process of complex personal development. The aim of the present study is to examine the mission of Reformed colleges in relation to talent development by highlighting two examples: the role of the Reformed College in Sárospatak and of that in Pécs in supporting talent. The sources used were school bulletins and yearbooks.